2000
DOI: 10.1021/je000060k
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tensions, Refractive Indexes and Excess Molar Volumes of Hexane + 1-Alkanol Mixtures at 298.15 K

Abstract: Surface tensions and refractive indexes for binary mixtures of {hexane + ethanol, + 1-propanol, + 1-butanol, + 1-pentanol, + 1-hexanol, + 1-heptanol, and + 1-octanol} have been measured at 298.15 K. Surface tension deviations and changes of refractive index have been also calculated. Excess molar volumes of {hexane + ethanol, + 1-pentanol, and + 1-hexanol} mixtures have been determined at 298.15 K from density data and compared with literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(65 citation statements)
references
References 15 publications
9
56
0
Order By: Relevance
“…1 shows the surface tensions of n-nonane + 1-hexanol at the three temperatures. The behaviour is standard, σ is observed to decrease with increasing T. In addition, and comparing with the literature values [13,21,22] the surface tension increases with the length of the n-alkane and 1-alkanol molecular chains (see Fig. 2).…”
Section: Density and Surface Tensionsupporting
confidence: 78%
See 3 more Smart Citations
“…1 shows the surface tensions of n-nonane + 1-hexanol at the three temperatures. The behaviour is standard, σ is observed to decrease with increasing T. In addition, and comparing with the literature values [13,21,22] the surface tension increases with the length of the n-alkane and 1-alkanol molecular chains (see Fig. 2).…”
Section: Density and Surface Tensionsupporting
confidence: 78%
“…The measured density and surface tension of the pure liquids (n-nonane and 1-hexanol) at 288.15, 298.15 and 308.15 K are listed in Table 1 together with those values found in the literature [10][11][12][13][14][15][16][17][18][19][20]. The agreement, within the experimental uncertainties for most values, ensures both the purity of the chemicals used and the experimental devices accuracy.…”
Section: Density and Surface Tensionsupporting
confidence: 53%
See 2 more Smart Citations
“…Anwar discussed changes in the values of excess thermodynamic properties with the change in composition and the temperature and their impact on hydrogen bonds and their effect on the mixing process [25]. Shekaari et al used the excess properties in studying the polymer's effectiveness and demonstrated increased effectiveness by increasing the molar mass of polymer [26]. From above survey we conclude that 1-Butanol and Ethyl acetate are important solvents and have been used in many industrial processes and there is a need for thermodynamic process data which is the basis for theoretical and design purposes.…”
Section: Introductionmentioning
confidence: 99%